The emperor and the elephant: Christians and Muslims in the age of Charlemagne - Ottewill-Soulsby, Sam (Princeton University Press, 2023)
"In the year 802, an elephant arrived at the court of the Emperor Charlemagne in Aachen, sent as a gift by the ʻAbbāsid Caliph, Harun al-Rashid. This extraordinary moment was part of a much wider set of diplomatic relations between the Carolingian dynasty and the Islamic world, including not only the Caliphate in the east but also Umayyad al-Andalus, North Africa, the Muslim words of Italy and a varied cast of warlords, pirates and renegades. 'The Emperor and the Elephant' offers a new account of these relations. By drawing on Arabic sources that help explain how and why Muslim rulers engaged with Charlemagne and his family, Sam Ottewill-Soulsby provides a fresh perspective on a subject that has until now been dominated by and seen through western sources. 'The Emperor and the Elephant' demonstrates the fundamental importance of these diplomatic relations to everyone involved. Charlemagne and Harun al-Rashid's imperial ambitions at home were shaped by their dealings abroad. Populated by canny border lords who lived in multiple worlds, the long and shifting frontier between al-Andalus and the Franks presented both powers with opportunities and dangers, which their diplomats sought to manage. Tracking the movement of envoys and messengers across the Pyrenees, the Mediterranean and beyond, and the complex ideas that lay behind them, this book examines the ways in which Christians and Muslims could make common cause in an age of faith."--